Effect of salinity on water/oil interface with model asphaltene and non-ionic surfactant: Insights from molecular simulations. (1st May 2023) - Sun, Xiaoyu; Zeng, Hongbo; Tang, Tian
Highlights: Adsorption free energy of demulsifier is higher than that of model asphaltene and is more strongly affected by NaCl addition. Model asphaltene and demulsifier form complexes at water/heptol interface. NaCl concentration has a non-monotonic effect on the IFT of water/heptol interface. Model asphaltene lowers the transition concentration in the non-monotonic trend. Abstract: Water or brine always co-exist with oil during petroleum production, often in the form of emulsions which can be stabilized by surface-active components such as asphaltenes. Polymeric demulsifiers were frequently applied to destabilize the water/oil interface. To understand the demulsification mechanisms of water/oil emulsion, it is important to understand the effect of salinity on the stability of water/oil interface with adsorbed asphaltenes and polymeric demulsifiers. In this work, molecular dynamics simulations were performed on water/heptol interfaces under the influence of a model asphaltene (VO-79), a polymer demulsifier (PEO5 -PPO10 -PEO5 ) and varying concentrations of NaCl. Potential of mean force calculation indicated that when NaCl was added the magnitude of the adsorption free energy for VO-79 had insignificant changes and that for the polymer increased. In the absence of VO-79, the interfacial tension (IFT) at the water/heptol interface first increased upon increasing the NaCl concentration to 6 wt% and then decreased. The initial increase was attributed to the negative surface excess of salt while the subsequent decrease was due to the evident aggregation of salt ions in the water phase. With both polymer and VO-79 at the interface, the effect of salinity on IFT followed the same non-monotonic trend, except that the transition occurred at a lower concentration, which was caused by the mutual influence of H-bonds between adsorbates and water, and the surface excess of salt. The results provide useful insights into the effect of salinity on the stabilization and destabilization of water/oil interface.